Association between exposure to proton pump inhibitors and delirium: a descriptive and disproportionality analysis of VigiBase - Decros, Alexandre; Minoc, Elise-Marie; Lelong‐Boulouard, Véronique; Chrétien, Basile; Meurant, Alexandre; Alexandre, Joachim; Dolladille, Charles; Villain, Cédric (BMJ Open, 2024)
OBJECTIVES: Proton pump inhibitor (PPI) exposure can lead to hyponatraemia, which is a common cause of delirium. An association between PPI exposure and delirium without hyponatraemia has been suggested in the literature. We aimed to describe the association between reports of delirium and PPI exposure and to assess the association between PPI and delirium with and without hyponatraemia. DESIGN: A descriptive and disproportionality analysis of claims data. SETTING: World pharmacovigilance database VigiBase between 1 January 1991 and 9 February 2022. PRIMARY AND SECONDARY OUTCOME MEASURES: In the first part, we described reports of delirium for which involvement of a PPI or interactions of PPIs with other drugs were suspected. In the second part, delirium cases and non-cases were used to assess the disproportionality signal using the reporting OR (ROR) for the associations of PPI exposure with delirium or delirium/hyponatraemia co-events. RESULTS: We identified 2395 reports of delirium in which involvement of PPI exposure was suspected. Omeprazole, esomeprazole and pantoprazole were the most frequently reported PPIs. Hyponatraemia was present in 11% of the reports. The disproportionality analysis included 1 264 798 reports of adverse drug reactions in patients using PPIs, including 19 081 reports of delirium. We did not find a disproportionality signal for the association between PPI use and delirium (ROR 0.89, 95% CI 0.87 to 0.91). We detected an association of PPI use with delirium/hyponatraemia co-events (ROR 1.53, 95% CI 1.41 to 1.65). CONCLUSIONS: Most reports of delirium in which the involvement of PPIs was suspected did not include concomitant hyponatraemia. However, no significant signal of disproportionate reporting of delirium was observed for PPIs compared with other drugs, except in cases of delirium associated with hyponatraemia. Hyponatraemia may be the main mechanism linking PPI exposure with delirium, and this possibility should be further explored in prospective studies. TRIAL REGISTRATION NUMBER: NCT05815550.